1971
DOI: 10.1128/iai.3.5.678-687.1971
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Hemolytic Activities of Escherichia coli

Abstract: Some properties of the cell-free and cell-associated hemolysins of Escherichia coli were studied. Several strains of E. coli that were isolated from intestines of pigs with edema disease produce large quantities of cell-free hemolysin when grown in the presence of an extract of meat. The component of meat that stimulates production of cell-free hemolysin is not extracted by lipid solvents and is not dialyzable. The cell-free hemolysin is an acidic substance that occurs in two forms. It is inactivated by trypsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
0
1

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 11 publications
2
46
0
1
Order By: Relevance
“…Sakazaki et al (1971) found that basal media containing a high content of animal tissue extracts sthulated haemolysis by V. cholerae in culture. Similar observations of increased haemolysin production by E. coli in media containing animal tissue extracts were made by Short & Kurtz (1971). It appears that, as with V. cholerae or E. coli, the campylobacters have complex requirements to stimulate haemolysis in culture.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Sakazaki et al (1971) found that basal media containing a high content of animal tissue extracts sthulated haemolysis by V. cholerae in culture. Similar observations of increased haemolysin production by E. coli in media containing animal tissue extracts were made by Short & Kurtz (1971). It appears that, as with V. cholerae or E. coli, the campylobacters have complex requirements to stimulate haemolysis in culture.…”
Section: Discussionsupporting
confidence: 63%
“…Peptones and extracts from animal tissue stimulate haemolytic activity or production of haemolysin in culture media by certain Gram-negative bacteria, e.g. eltor strains of Vibrio cholerae (Sakazaki et al 1971) and strains of Escherichia coli (Short & Kurtz 1971). It was therefore decided to use Heart Infusion (HI; Difco) and Brain Heart Infusion (BHI; Oxoid) which both contain high concentrations of animal tissue extracts, to study haemolytic activity of the campylobacters.…”
Section: Media F O R Testing H a E M O L Y S I Smentioning
confidence: 99%
“…Alpha-hemolysins expressed by E. coli from a variety of sources are antigenically cross-reactive (33) and have similar, although not identical, physical properties. They are, in general, heat labile (4,18,27,33,38,42), acidic (21,27,31) proteins (18,27,31,42) with a molecular weight of 58,000 (10) to 120,000 (41). They require Ca2+ for full activity (28,31,39) and are most active at pHs 7 to 8 (31,42).…”
mentioning
confidence: 99%
“…HlyA is thought to lyse cells by forming pores in the membranes of target cells (2)(3)(4)15). The hemolytic activity of HlyA is calcium dependent (1,28,29,31). In a preceding paper, we demonstrated that the binding of E. coli hemolysin to erythrocytes is calcium dependent (5).…”
mentioning
confidence: 99%